"Be a badass with a good ass": race, freakery, and postfeminism in the #StrongIsTheNewSkinny beauty myth. Issue 2 (17th February 2021) - Maddox, Jessica
ABSTRACT: #StrongIsTheNewSkinny has become a bodily mantra found across social media, and it is a postfeminist beauty myth. But given postfeminist contradictions, this presents a terrain in which only certain women are even allowed to attempt to achieve the unobtainable body. This is compounded by race and cisgenderism. To unpack this tenuous relationship, this work uses critical discourse analysis to examine image macros associated with the hashtag. The key themes that emerged were two-fold: First, #StrongIsTheNewSkinny does not actually seek visible strength, and it functions as rhetorical strength—it calls for strength but does not actually seek it in response. In this way, #StrongIsTheNewSkinny repackages old body stereotypes in a way befitting the era of postfeminist confidence. Two, this further marginalizes women of color, as a discourse purporting to reject the ultrathin continues to reinforce a particular type of White, thin, cisgendered female body. The analysis of this hashtagged beauty myth fits into a trend of only rhetorically posing cultural issues—diversity may be called for, but it is not actively sought in response. This is worth noting as feminism turns to the fourth wave and emphasizes hashtags—hashtags can turn and remain rhetorical if not critically probed.